Early Diagnosis of Oral Cancer: Dentists, Oral Pathologists Working Together - Vinall, Phil (MD Conference Express, 2014)
Oral cancer is a highly destructive disease that is associated with significant morbidity. Surgery with follow-up radiation is the most common treatment but almost always leaves patients with obvious physical changes and functional deficits. Because the size of the tumor determines the extent of the surgery, early diagnosis and intervention offer the best chances to survive and minimize these effects. This article discusses early identification of oral tissue changes that may indicate oral cancer and argued in favor of an ongoing relationship between dentists and oral pathologists as a way of optimizing patient care.